Glial cell line‐derived neurotrophic factor increases matrix metallopeptidase 9 and 14 expression in microglia and promotes microglia‐mediated glioma progression. Issue 4 (6th January 2021) - Huang, Yimin; Zhang, Baole; Haneke, Hannah; Haage, Verena; Lubas, Malgorzata; Yuan, Yang; Xia, Pengfei; Motta, Edyta; Nanvuma, Cynthia; Dzaye, Omar; Hu, Feng; Kettenmann, Helmut
Abstract: Glial cell line‐derived neurotrophic factor (GDNF) is released by glioma cells and promotes tumor growth. We have previously found that GDNF released from the tumor cells is a chemoattractant for microglial cells, the immune cells of the central nervous system. Here we show that GDNF increases matrix metalloproteinase (MMP) 9 and MMP14 expression in cultured microglial cells from mixed sexes of neonatal mice. The GDNF‐induced microglial MMP9 and MMP14 upregulation is mediated by GDNF family receptor alpha 1 receptors and dependent on p38 mitogen‐activated protein kinase signaling. In organotypic brain slices, GDNF promotes the growth of glioma and this effect depends on the presence of microglia. We also previously found that MMP9 and MMP14 upregulation can be mediated by Toll‐like receptor (TLR) 2 signaling and here we demonstrate that GDNF increases the expression of TLR1 and TLR2. In conclusion, GDNF promotes the pro‐tumorigenic phenotype of microglia. Abstract : Glial cell line‐derived neurotrophic factor derived from glioma cells upregulate matrix metallopeptidase 9 and 14 expression on microglia, which in turn promote glioma progression.